Mannitol has a protective effect on testicular torsion: An experimental rat model. Issue 3 (June 2016) - Kurt, Omer; Yazici, Cenk Murat; Erboga, Mustafa; Turan, Cuneyt; Bozdemir, Yeliz; Akbas, Alpaslan; Turker, Polat; Aktas, Cevat; Aydin, Murat; Yesildag, Ebru
Summary: Objective: Testicular torsion is an emergency condition that causes testicular injury. Any treatment opportunity reducing the destructive effect of testicular torsion is important for the future life of patients. In this experimental study we investigated the protective effect of mannitol on ischemia–reperfusion (I/R) injury in a rat testes torsion model. Method: In total, 32 male Sprague Dawley rats were included. Four experimental groups included eight rats each. Group A was a sham group in which the right testis was brought out through a scrotal incision and then replaced in the scrotum without torsion. In Group B, the right testis was torsioned, by rotating 720° clockwise and fixed to the scrotum with no treatment. In Group C, the same testicular torsion process was performed with saline infusion just after testicular torsion. In group D, mannitol infusion was used just after testicular torsion. Testicles were detorsioned after 3 h and left inside for more than 2 h before orchiectomy. Histopathological, immunohistochemical, and biochemical analyses were performed. Results: Testicular architecture was disturbed significantly in the torsion groups without mannitol infusion. However, testicular tissue structure was significantly better in the mannitol-treated group, demonstrating a protective effect. Similar findings were also shown for the proliferating cell nuclear antigen (PCNA) index and antioxidant activity; both were higher in the mannitol group than in the no-treatment and saline groups ( p < 0.01). The apoptotic index was also significantly lower in the mannitol-treated group compared with the no treatment and saline groups ( p < 0.01). Conclusions: The seminiferous tubule structure in testicular torsion without mannitol treatment was significantly disturbed, whereas the structural disruption was considerably less in the mannitol group. Mannitol treatment also decreased reactive oxygen radical levels significantly and was able to decrease apoptosis. These results were consistent with other organ model studies that evaluated the protective effects of mannitol treatment in I/R injury. Mannitol infusion had a protective effect against I/R injury in testicular torsion in rats. This experimental study may guide clinicians to evaluate the effectiveness of mannitol in human testicular torsion. Table Histopathological evaluation of study groups. Apoptotic index PCNA index MTBS MSTD Group A 3.88 ± 0.83 b 36.47 ± 1.36 b 9.23 ± 0.17 b 273.25 ± 5.14 b Group B 25.88 ± 2.91 a, b 22.22 ± 2.34 a, b 4.57 ± 0.22 a, b 209 ± 6.11 a, b Group C 25.52 ± 2.87 a, b 22.51 ± 2.99 a, b 4.76 ± 0.14 a, b 210.63 ± 5.09 a, b Group D 15.25 ± 1.48 a 29.28 ± 1.66 a 6.72 ± 0.25 a 229.63 ± 6.18 a MSTD = mean seminiferous tubular diameter; MTBS = mean testicular biopsy score; PCNA = proliferating cell nuclear antigen; I/R = ischemia-reperfusion. Group A was a sham operation group, Group B (I/R) had 3 h ischemia and 2 h reperfusion, Group C (I/R + Saline) had 3 h ischemia and 2 h reperfusion and saline bolus treatment, Group D (I/R + Mannitol) had 3 h ischemia and 2 h reperfusion and mannitol bolus treatment. a p < 0.01 compared with group A. b p < 0.01 compared with group D.